(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
The present article describes the attempt to construct a scale to measure the social media addiction among adolescent students. Eventually, pilot study was conducted on a 100 students studying in Standard XI th from Government schools in Chennai district. The Cronbach alpha method and item total correlation was done to find out the reliability and validity of the Social Media Addiction(SMA)Scale. The face validity and content validity was found out with the help of experts.